What makes music emotionally significant? Exploring the underlying mechanisms. (July 2014) - Juslin, Patrik N.; Harmat, László; Eerola, Tuomas
A common approach to study emotional reactions to music is to attempt to obtain direct links between musical surface features such as tempo and a listener's response. However, such an analysis ultimately fails to explain why emotions are aroused in the listener. In this article, we propose an alternative approach, which seeks to explain musical emotions in terms of a set of underlying mechanisms that are activated by different types of information in musical events. We illustrate this approach by reporting a listening experiment, which manipulated a piece of music to activate four mechanisms: brain stem reflex; emotional contagion; episodic memory; and musical expectancy. The musical excerpts were played to 20 listeners, who were asked to rate their felt emotions on 12 scales. Pulse rate, skin conductance, and facial expressions were also measured. Results indicated that target mechanisms were activated and aroused emotions largely as predicted by a multi-mechanism framework.